Japanese Higher Education Policy in Korea (1910—1945) - Jeong-Kyu Lee (Arizona State University, 2002)
The purpose of this article is to examine the impact of Japanese nationalistic thought on the administrative systems and structures of colonial and modern higher education in Korea, as well as to analyze Japanese higher educational policy in Korea during the colonial period (1910-1945). It begins with an examination of Shinto, a syncretistic Japanese state religion and the ideological basis of national education. The author investigates Japanese educational policy and administration during the colonial period, including the establishment of a colonial imperial university in Korea. He also reviews the administrative systems and organizational structures in imperial and colonial universities. Both beneficial and negative impacts of the Japanese colonial education system on current Korean higher education conclude the analysis.